In the Field of Public Education of Uzbekistan Measures to Struggle Against Offenses and their Results (on the Example of Kashkadarya Region) - Sharopova, N. А. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article analyzes cases of juvenile delinquency in Uzbekistan over the years of independence in the case of public schools in the Kashkadarya region and explains the causes and causes of increased youth crime rates across the district.